PENYELESAIAN SENGKETA SERTIPIKAT GANDA PADA PTUN - Sandy Sulistiono; Widyawati Boediningsih (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The diversity of Indonesia's resources from land and sea has been recognized by the world. With this diversity of resources, the country certainly needs a legal umbrella to provide protection so that the potential of these natural resources is maintained into the future. So in this case, the state is in the position of "ruler" which has the authority to regulate the use of existing earth, water and space, as stated in Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. One embodiment of this article is the issuance of the UUPA which provides opportunities Indonesian citizens to own a plot of land in their own name, proven by ownership of a certificate. However, during the journey, a discrepancy was discovered that 1 plot of land was owned by 2 certificates, which created a sense of legal uncertainty for the owner. Therefore, this research will examine whether the problem of double certificates can be resolved at the TUN judicial body. Because this research is legal research, the approach used is a conceptual approach related to the concept of KTUN and TUN procedural law which is supported by a statutory approach using currently applicable provisions such as referring to the Constitution and other derivative regulations, KTUN,